Developing Multifunctional Serial-Parallel Data Communication Interface for PC-Based Control System - Yuliadi Erdani (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
Today, Personal Computers (PC) have increasing role in measurement and control technology. The more and more complex processes in many fields of technique and research can often be controlled only by programmable control systems. The PC-based control system is an alternative and smart solution of programmable control systems. One important thing of the PC-based control system is the serial-parallel data communication. Problems and difficulties with hardware and software concerning serial-parallel data transmission have been discussed in many literatures and are still the important consideration of building PC-based control systems. To overcome mentioned problem, a multifunctional serial-parallel data communication interface has been developed.This paper describes the development of the interface that covers its design and implementation and the discussion of software and hardware problems, and the solutions.Keywords: technique, pc-based control system, data communication